2015
DOI: 10.1021/bi501221a
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Catalase-Peroxidase Large Loop 2 Revealed by Deletion Mutagenesis: Control of Active Site Water and Ferric Enzyme Reactivity

Abstract: Catalase-peroxidases (KatGs), the only catalase-active members of their superfamily, all possess a 35-residue interhelical loop called large loop 2 (LL2). It is essential for catalase activity, but little is known about its contribution to KatG function. LL2 shows weak sequence conservation; however, its length is nearly identical across KatGs, and its apex invariably makes contact with the KatG-unique C-terminal domain. We used site-directed and deletion mutagenesis to interrogate the role of LL2 and its inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…108 Furthermore, the structure of KatG contains a large loop, not present in the peroxidase, which is essential for catalase activity. 109, 110 It is believed that heme is required to generate the cross-linked amino acids during the maturation of the active site. 111 The cross-linked amino acids in addition to the heme are then for its catalatic activity.…”
Section: Cross-linked Amino Acids In Metalloproteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…108 Furthermore, the structure of KatG contains a large loop, not present in the peroxidase, which is essential for catalase activity. 109, 110 It is believed that heme is required to generate the cross-linked amino acids during the maturation of the active site. 111 The cross-linked amino acids in addition to the heme are then for its catalatic activity.…”
Section: Cross-linked Amino Acids In Metalloproteinsmentioning
confidence: 99%
“…However, the Met-Tyr-Trp cross-link is only seen in KatG, and site-directed mutagenesis studies demonstrated that the cross-link is needed for the catalatic activity, but not for peroxidatic activity . Furthermore, the structure of KatG contains a large loop, not present in the peroxidase, which is essential for catalase activity. , It is believed that heme is required to generate the cross-linked amino acids during the maturation of the active site . The cross-linked amino acids in addition to the heme are then required for its catalatic activity.…”
Section: Cross-linked Amino Acids In Metalloproteinsmentioning
confidence: 99%
“…Among them are two large loops (LL1 and LL2), both of which are essential for KatG function (20 -22, 26, 27). Both loops also contribute to a much narrower channel to the active-site heme, which among other things restricts access of many peroxidatic electron donors (PxEDs) to the heme edge (22,(27)(28)(29). Additionally, LL1 bears an invariant tyrosine (Tyr-229 by MtKatG numbering) that participates in a unique methionine-tyrosine-tryptophan (MYW) adduct that serves as a protein-derived cofactor (20 -22, 30, 31).…”
mentioning
confidence: 99%
“… 13 , 14 Mutation of any of these KatG-typical structural features typically reduces the catalase activity without compromising the peroxidase activity. 13 22 …”
mentioning
confidence: 99%
“…Similar to the prokaryotic counterparts, eukaryotic KatGs have two interdependent cooperating redox-active cofactors at their active site, namely a heme b and a unique posttranslationally and autocatalytically formed Met299-Tyr273-Trp140 (MYW) adduct [extracellular Magnaporthe grisea KatG ( Mag KatG2) numbering throughout]. KatG can be described as a catalase in peroxidase clothing because it has been engineered by Nature to catalyze efficient H 2 O 2 dismutation similar to monofunctional catalases. , Together with cytochrome c peroxidases, ascorbate peroxidases and hybrid-type peroxidases KatGs comprise Family I of the peroxidase-catalase superfamily. , Besides the MYW adduct mentioned above, further KatG-specific structural peculiarities include (i) a two-domain structure with only the N-terminal domain containing the two redox cofactors and essential catalytic residues, ,, (ii) loop insertions that contribute to the architecture of the long and restricted access channel, and (iii) a fully conserved aspartate at the entrance of the substrate channel to the heme cavity. , Mutation of any of these KatG-typical structural features typically reduces the catalase activity without compromising the peroxidase activity. …”
mentioning
confidence: 99%